2016
DOI: 10.1007/s12160-016-9814-8
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Online and In-Person Social Networks for Physical Activity: A Randomized Trial

Abstract: Background Social networks can influence physical activity, but little is known about how best to engineer online and in-person social networks to increase activity. Purpose To conduct a randomized trial based on the Social Networks for Activity Promotion model to assess the incremental contributions of different procedures for building social networks on objectively-measured outcomes. Methods Physically inactive adults (n = 308, age, 50.3 (SD = 8.3) years, 38.3% male, 83.4% overweight/obese) were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 58 publications
(89 reference statements)
5
45
0
Order By: Relevance
“…This is echoed by the findings of another study advocating for a more tailored approach to tracking activities salient to older adults [39]. Additionally, our findings regarding social support strengthened the evidence from previous studies where social support has been found to be one of the most important and consistent predictors of physical activity adherence [40][41][42][43].…”
Section: Comparison With Prior Worksupporting
confidence: 83%
“…This is echoed by the findings of another study advocating for a more tailored approach to tracking activities salient to older adults [39]. Additionally, our findings regarding social support strengthened the evidence from previous studies where social support has been found to be one of the most important and consistent predictors of physical activity adherence [40][41][42][43].…”
Section: Comparison With Prior Worksupporting
confidence: 83%
“…Social factors such as social support or competition have been shown to increase engagement, adherence, and completion in physical activity interventions (18, 45, 49, 50). Social support could involve having a friend or family member who supports one becoming more active, or having someone with whom to walk or exercise.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…Further, some have found that social support for physical activity is particularly important for those who are not regular exercisers (51). This is likely why others report social support is especially effective for increasing physical activity in inactive, unmotivated adults (49). Another social factor, competition, could involve competing against another to accumulate more steps or activity.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…Interventions targeting behavioural weight loss , healthy diet and PA have increasingly looked to online social media , commercially available dietary and PA apps , and related wearable electronic PA trackers to enhance outcomes by promoting social support and self‐monitoring of diet and PA . This research has paralleled the growing popularity of commercially available PA‐focused and dietary‐focused smartphone apps and wearable PA tracking devices .…”
Section: Introductionmentioning
confidence: 99%
“…Interventions targeting behavioural weight loss (16)(17)(18)(19)(20), healthy diet (21,22) and PA (21)(22)(23)(24)(25)(26)(27)(28) have increasingly looked to online social media (16,17,(22)(23)(24)(25)(26), commercially available dietary and PA apps (17)(18)(19)(20)(21)(22)27,28), and related wearable electronic PA trackers (18,(20)(21)(22)27,28) to enhance outcomes by promoting social support (16,17,19,(21)(22)(23)(24)(25)(26) and self-monitoring of diet and PA (17)(18)(19)(20)…”
Section: Introductionmentioning
confidence: 99%